Socialization and Technical Guidance of Road Specifications to Glodog Village Appliances, Palang District, Tuban Regency in the Framework of Village Road Development - Sugiyanto; Widya, Liadira Kusuma; Susanto, Harry; Octavia, Syarifah Nur (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
Roads are an indispensable infrastructure in supporting community economic activities, both in urban and rural areas. This community service activity was carried out with the aim of providing socialization and technical guidance on road specifications to the Glodog Village Government apparatus, Palang, Tuban East Java, in the context of village road construction. This theme was chosen because of the problem of proposing village roads to Regional Apparatus Organization (OPD) who do not have the authority to handle them. The method used is to hold a face-to-face meeting followed by participants consisting of village government officials, the head of the BPD and community leaders in Glodog Village, Palang District, Tuban East Java. The results of the implementation of this community activity went quite smoothly, followed quite enthusiastically, and received a warm welcome because it provided very useful knowledge in the construction of village roads. To get more optimal benefits, it is recommended that further socialization activities involve elements of OPD and contractors so that all problems encountered can be solved in a directed and integrated manner.